Synthesis and Characterization of CuO/C Catalyst for the Esterification of Free Fatty Acid in Rubber Seed Oil - Khan, Maksudur R.; Huei, Ruey Ong; Yousuf, Abu; Chowdhury, M. N. K.; Cheng, C. K. (Elsevier, 2014)
Plant oils or animal fats that contain high free fatty acid (FFA) are not preferred for base catalyzed biodiesel production. Pre-esterification is widely used to reduce the FFA content of the oil for avoiding saponification and associated purification cost. In the present study, carbon supported copper oxide (CuO/C) catalyst was prepared for the esterification of FFA in the rubber seed oil (RSO) which was extracted from the fresh seed by soxhlet extractor using hexane as a solvent. Copper nanoparticles were synthesized by sol–gel method and the nanoparticles were impregnated into the pore network of the carbon support. The copper impregnated activated carbon powder was calcined at 400 °C in a furnace for 6 h, leading to the formation of CuO/C. The catalyst was characterized by using Brunauer Emmett Teller, X-ray photoelectron spectroscopy, Energy-dispersive X-ray spectroscopy and Thermogravimetric analysis. Moreover, Hammett indicator method was used to determine the acidity of the catalyst. The effects of reaction temperature, methanol/FFA molar ratio, catalyst concentration on the FFA conversion were also studied. Based on the experimental results, methanol to FFA ratio of 10:1, catalyst dose 8 wt%, reaction time of 6 h and temperature 65 °C were found as the optimum for the esterification reaction. Therefore, the developed catalyst could be effectively used for the esterification of FFA in plant oil.